Preisbildung bei Semestertickets bezieht alle Studenten mit ein. - Peistrup, Matthias; Stingel, Susanne (Deutscher Verkehrs-Verl., 2007)
In vielen deutschen Universitätsstädten steht regelmäßig ein kontrovers diskutiertes Thema auf der Agenda von Verkehrsunternehmen, Studierenden und Politik: das Semesterticket. Mit einem Semesterticket können die Studierenden Busse und Bahnen des Nahverkehrs gegen einen festen Semesterbeitrag meist unbegrenzt und ohne Zusatzkosten nutzen. Die Nutzungsbedingungen und der Preis für dieses Ticket werden zwischen den Studierenden auf der einen und den Verkehrsunternehmen auf der anderen Seite in Verhandlungen festgelegt. difu

In many German university towns there are student tickets for public transport. These tickets often are flatrate tickets: students are eligible to use public transport within a defined area for a certain period (i.e. 6 months). In most cases, it is mandatory to buy the ticket when inscribing for a semester. The price for such ticket is determined in negotiations between the student body and the respective transportation company. The article presents theoretical foundations and application of a method for determining a price which is acceptable for both negotiating partners. By means of limit conjoint analysis, a cumulative willingness-to-pay is determined. This represents the price from the viewpoint of the student body. Opportunity cost analysis is used to identify the bottom price from the viewpoint of the transportation companies. These price points mark the boundaries within which there is room to negotiate an acceptable price for the student ticket. difu
Keywords: Öffentlicher Verkehr; Student; Verkehrsunternehmen; ÖPNV; Nahverkehr; Verkehrsnachfrage; Befragung; Preispolitik; Verkehrspreis; Subvention; Semesterticket; Fahrschein; Fallbeispiel